The contribution of the “seminar” teaching technique to the cognitive development of accounting students - Urrutia-Heinz, Michele (2022)
This study seeks to analyze whether the use of the seminar technique, an active technique, as a complementary tool to lecture and exercise resolution, influences the level of cognitive development of students. In methodological terms, a quasi-experiment was carried out with students of the 4th semester of Accounting Sciences of a Federal Institution of Higher Education. The results showed that the use of the seminar, regarding the levels "remember, apply and analyze", was able to influence the cognitive development of students.It is concluded that the use of the seminar technique, as a complementary instrument, can influence the level of cognitive development achieved by accounting students.